Pengaruh Fixed Mindset terhadap Motivasi Belajar Siswa pada Mata Pelajaran Dasar Teknik Ketenagalistrikan - Aisyah Amini; Ahyanuardi Ahyanuardi (Jurnal Pendidikan Teknik Elektro, 2023)
The purpose of this study was to determine the effect of a fixed mindset on student learning motivation in DTK subjects at SMK Negeri 1 Padang. This type of research is a type of quantitative descriptive research. The research instrument used in this study was a questionnaire consisting of beliefs about intelligence, talent, character, beliefs about challenges, difficulties, failures, the impact of effort on self-development, beliefs on criticism and other people's input, students' intrinsic and extrinsic motivation. Before conducting research the questionnaire or questionnaire was validated first by 3 lecturers of electrical engineering at FT-UNP, then a research trial was carried out on 40 students. The subjects of this research were 104 students from class X TITL at SMK Negeri 1 Padang. Before conducting data analysis, normality tests and linearity tests were carried out. The data analysis technique used is descriptive quantitative data analysis technique which includes mean, median, mode, standard deviation, frequency distribution tables, histograms, simple linear regression, coefficient of determination and F test. The results showed that the fixed mindset has a significant effect on student learning motivation in DTK subjects at SMK Negeri 1 Padang.